DESAIN TAQMAN PROBE SECARA IN SILICO SEBAGAI PENDETEKSI MUTASI PADA KODON 516 GEN rpoB Mycobacterium tuberculosis UNTUK METODE REAL-TIME PCR - Suryani, Dek Pueteri Dewi; Yustiantara, Putu Sanna; Yowani, Sagung Chandra (Metamorfosa: Journal of Biological Sciences, 2017)
The aim of this research was to in silico design of TaqMan probe . Design of TaqMan probe were conducted using software Clone Manager Suite 6 . As a template, the rpoB gene of M. tuberculosis H37Rv (accession number U12205.1) was used. The results of this research were 8 sequences such as, R516MV-2, R516MV-3, R516MV-4, R516MV-5, R516MV-7, R516MV-8, R516MV-11, R516MV-13. These sequences were met the criteria of TaqMan probe , such as length of nucleotide (23-28 nucleotide), Tm value (72ºC), %GC (50-58%), runs and repeats (?4 bases), dimer structure in accordance to the requirements and does not form hairpin structures. In addition, these sequences were met labeling criteria of TaqMan probe which are including the location of G bases and the number of G-C bases in sequences. Therefore, these sequences could be labeled by FAM (reporter) at 5' end and TAMRA (quencher) at 3' end. The conclusion of this research, the sequences were met the criteria of TaqMan probe. Therefore, it could be targeted to detect mutations at codon 516 with a change of aspartic acid into valine (G A C ? G T C) by using real-time PCR method.
Keywords: rpoB gen, In Silico, TaqMan Probe, Real-time PCR